Cell-free antigens from precocious Paracoccidioides brasiliensis culture induce a typical delayed-type hypersensitivity reaction - Fecchio, C. J. [UNESP]; Dias-Melicio, L. A. [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP]; Guimaraes, S. [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP]; Sartori, Alexandrina [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Cell-free antigens (CFAg) derived from Paracoccidioides brasiliensis have typically been used in immunodiffusion reactions for serodiagnosis or therapeutic follow-up of paracoccidioidomycosis patients. Thus, we investigated the usefulness of CFAg obtained from cultures at different ages, to evaluate cellular immunity by the footpad test, in experimental murine paracoccidioidomycosis. Male mice infected with P. brasiliensis 265 strain were challenged in the footpad with CFAg obtained from four- (4d CFAg) or 11-day-old cultures (11d CFAg). The increase in footpad swelling provoked by 4d CFAg and 11d CFAg was similar and showed significant difference in relation to control groups. However, the infiltrate pattern was strikingly different: 4d CFAg induced a predominant mononuclear infiltrate whereas 11d CFAg provoked a predominant polymophonuclear infiltrate. These different inflammatory patterns were associated with distinct electrophoretic characteristics. By comparison with 11d CFAg, 4d CFAg showed more numerous and intense bands, including a strong one of 43 kDa (gp43). These results suggest that CFAg derived from Pb 265 isolate can be used as a reagent to evaluate cellular immunity; however, the culture's age is critical because only young cultures are able to induce a typical mononuclear infiltrate. The efficacy of this new paracoccidioidin to assay the cellular immunity in infections caused by other P. brasiliensis isolates is under investigation.
Keywords: Paracoccidioides brasiliensis; cell-free antigens; delayed-type hypersensitivity reaction; gp43; murine paracoccidioidomycosis